Etika Komunikasi Antarpersonal Rasulullah Ketika Marah Di Dalam Buku Jangan Bikin Rasul Marah - Vedrand Gilang Wahyudi Haris (Al-Wa'iyah, 2025)
This research aims to understand the ethics of the Prophet Muhammad’s صلى الله عليه وسلم communication when he was angry, asdescribed in the book Jangan Bikin Rasul Marah. Good ethics are an essential means of fostering a harmonious social life.This study is a qualitative content analysis, in which documents and other data—both empirical and theoretical—are collected and analyzed for this thesis. The research findings reveal the ethical conduct of the Prophet Muhammad صلى الله عليه وسلم whenexpressing anger, based on statements found in the book Jangan Bikin Rasul Marah. The purpose is to recognize and understand proper communication ethics when angry by observing and emulating how the Prophet Muhammad صلى الله عليه وسلمmanaged his anger.